Evidence for an Independent Hydrogenosome-to-Mitosome Transition in the CL3 Lineage of Fornicates - Vargová, Romana; Hanousková, Pavla; Salamonová, Jana; Žihala, David; Silberman, Jeffrey D.; Eliáš, Marek; Čepička, Ivan (Frontiers in Microbiology, 2022)
Fornicata, a lineage of a broader and ancient anaerobic eukaryotic clade Metamonada, contains diverse taxa that are ideally suited for evolutionary studies addressing various fundamental biological questions, such as the evolutionary trajectory of mitochondrion-related organelles (MROs), the transition between free-living and endobiotic lifestyles, and the derivation of alternative genetic codes. To this end, we conducted detailed microscopic and transcriptome analyses in a poorly documented strain of an anaerobic free-living marine flagellate, PCS, in the so-called CL3 fornicate lineage. Fortuitously, we discovered that the original culture contained two morphologically similar and closely related CL3 representatives, which doubles the taxon representation within this lineage. We obtained a monoeukaryotic culture of one of them and formally describe it as a new member of the family Caviomonadidae, Euthynema mutabile gen. et sp. nov. In contrast to previously studied caviomonads, the endobiotic Caviomonas mobilis and Iotanema spirale, E. mutabile possesses an ultrastructurally discernible MRO. We sequenced and assembled the transcriptome of E. mutabile, and by sequence subtraction, obtained transcriptome data from the other CL3 clade representative present in the original PCS culture, denoted PCS-ghost. Transcriptome analyses showed that the reassignment of only one of the UAR stop codons to encode Gln previously reported from I. spirale does not extend to its free-living relatives and is likely due to a unique amino acid substitution in I. spirale’s eRF1 protein domain responsible for termination codon recognition. The backbone fornicate phylogeny was robustly resolved in a phylogenomic analysis, with the CL3 clade amongst the earliest branching lineages. Metabolic and MRO functional reconstructions of CL3 clade members revealed that all three, including I. spirale, encode homologs of key components of the mitochondrial protein import apparatus and the ISC pathway, indicating the presence of a MRO in all of them. In silico evidence indicates that the organelles of E. mutabile and PCS-ghost host ATP and H2 production, unlike the cryptic MRO of I. spirale. These data suggest that the CL3 clade has experienced a hydrogenosome-to-mitosome transition independent from that previously documented for the lineage leading to Giardia.